Non-state actors in state-driven development processes: the case of religious actors and foreign aid flows. Issue 1 (2nd January 2020) - Fourie, Willem
ABSTRACT: How should non-state actors engage state-led development processes? This article uses the theological notion of "religious bilinguality" as a conceptual basis for identifying three roles in which religious communities can engage the state-led process of foreign aid distribution. The roles range from being granted to claiming the right of participation. As "guests", religious actors are able to reinvigorate existing dialogue platforms; as "servants", they are able to map motivations for foreign aid disbursement; and as "prophets", religious actors can identify and address discrepancies in the definition and distribution of foreign aid.